ANALISIS MODEL PROBLEM BASED LEARNING MENGGUNAKAN QUASI EKSPERIMEN DESIGN TERHADAP HASIL BELAJAR IPA SISWA SMP aNEGERI 1 JORLANG HATARAN - Rosenta Purba, Ika (Jurnal Metabio, 2021)
The Problem-Based Learning (PBL) model, or problem-based learning, is essential for science classes at the junior high school (SMP) level. This learning model can improve students' thinking skills, instill personal and social character values, and foster academic achievement through improved student learning outcomes. This study demonstrated a higher average post-test score (8.04) compared to the control class that did not implement the PBL model (6.87), a difference of 1.17 points.